Field notes contributed by James J. Dinsmore, spring 1979 - Dinsmore, James J.et al (1979)
Spring report of birds contributed by James J. Dinsmore. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1979. Epson - sheet feed/flatbed